Marcel Gauchet, lecteur critique de Jürgen Habermas - Camille Roelens (Recherches Germaniques)
The purpose of this article is to study the references made by Marcel Gauchet to the thought of Jürgen Habermas. Being in presence of two major contemporary intellectuals, both of them having proposed a comprehensive historical and philosophical interpretation of democratic modernity, gives this intertextual approach a clear theoretical and heuristic interest. The first part shows that a fundamental point of convergence between the two approaches is critical vigilance in the face of antimodern thoughts. A second part highlights Gauchet’s inspirations, which can safely be described as Habermasian. A third part aims to highlight the limits of Habermas’ modernity thinking for Gauchet, in particular to understand the current situation of Western democracies. A fourth part brings out and discusses certains points where Gauchet intends to distance himself from Habermasian proposals concerning the generating fact of democratic modernity and conceptions of citizenship.